Design Parametric Optimization Of Wall Following Robot - et. al., D.Elayaraja, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, the trajectory tracking control of mobile robots has been a subject of research. This aim of the work is to achieve a minimum path traveling time of the wall following robot by optimizing the design parameters of the robot. The input parameters are wheel diameter, caster wheel position and turn radius. The output parameter is the tracking time. Three levels of wheel size, castor wheel position and turn radius are considered. The methods used are Taguchi method, Hybrid Neural network fuzzy logic method and Genetic algorithm.The values obtained from neural network algorithm are very close to the experimental value.